(untitled) (Medico Legal Update, 2021)
Background/Objectives: The purpose of this study is to evaluate the prevalence and related risk factors of problem drinking in the Korean elderly population. Method/Statistical Analysis: Participants (n=817) aged 65 years or older were selected from the Korea National Health and Nutrition Examination Survey [KNHANES] of 2018. Sociodemographic characteristics and AUDIT-C score were obtained from the KNHANES dataset. AUDIT-C scores were categorized into two groups, including low risk, high-risk alcohol drinking according to WHO guidelines. Data analysis was performed using SPSS WIN 25.0 program. Findings: In this study, the prevalence of high-risk alcohol drinking was 31.9%, respectively. Adjusted mean AUDIT score was higher in men, younger elderly individuals, as well as those with lower education levels and those that smoked. Results revealed that demographic variables, including sex, age, education level, and smoking, were important factors affected high-risk drinking. In particular, since family number and smoking were the most significant risk factor, the odds ratio for high-risk drinking among participants that smoked was 2.49 [(95% confidence interval (CI)=1.31-4.71)]. Improvements/Applications: This study suggests that men, younger age, low educational level, and smoking are the risk factors for a high-risk alcohol drinking